Syrian Journalists’ Use of Data Available on Web 2.0: An Analytical Study - مهنا عبد المجيد; ملحم محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study dealt with the topic of Web 2.0 sites, their characteristics and importance for workers in the journalistic field to search for data and use it in preparing articles and analyzing its elements, and the most important services they provide; The study aimed to analyze the behavior of journalists in using this data. In addition to learning about Web 2.0 properties and their importance for journalists. In his study, the researcher used the descriptive and analytical method, and the questionnaire was used as a main tool for the study. The random sample was relied upon to choose the research sample that was withdrawn from the Syrian researchers using scientific networks, which amounted to 50 users. The study reached several results, the most important of which are: